2016 IEEE 13th International Conference on Wearable and Implantable Body Sensor Networks (BSN) 2016
DOI: 10.1109/bsn.2016.7516235
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning for human activity recognition: A resource efficient implementation on low-power devices

Abstract: Abstract-Human Activity Recognition provides valuable contextual information for wellbeing, healthcare, and sport applications. Over the past decades, many machine learning approaches have been proposed to identify activities from inertial sensor data for specific applications. Most methods, however, are designed for offline processing rather than processing on the sensor node. In this paper, a human activity recognition technique based on a deep learning methodology is designed to enable accurate and real-tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
125
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(130 citation statements)
references
References 19 publications
0
125
0
5
Order By: Relevance
“…Ronao and Cho () have proposed multilayer CNN model with alternating convolutional and pooling layers and showed that their proposed model outperforms the state‐of‐the‐art accuracy for ADLs which were recorded by the authors from 30 different users. Ravi, Wong, Lo, and Yang () have used short‐term Fourier transform of the accelerometer data as an input to the proposed CNN network and have achieved accuracy close to the state‐of‐the‐art results. Bhattacharya and Lane () have designed and developed a restricted Boltzmann machine (RBM)‐based AR model for smart watches and have proved that the model does not have any hardware constraints.…”
Section: Deep Learning In Armentioning
confidence: 72%
“…Ronao and Cho () have proposed multilayer CNN model with alternating convolutional and pooling layers and showed that their proposed model outperforms the state‐of‐the‐art accuracy for ADLs which were recorded by the authors from 30 different users. Ravi, Wong, Lo, and Yang () have used short‐term Fourier transform of the accelerometer data as an input to the proposed CNN network and have achieved accuracy close to the state‐of‐the‐art results. Bhattacharya and Lane () have designed and developed a restricted Boltzmann machine (RBM)‐based AR model for smart watches and have proved that the model does not have any hardware constraints.…”
Section: Deep Learning In Armentioning
confidence: 72%
“…In (Singh et al, 2017), pressure sensor data was transformed to the image via modality transformation. Other similar work include (Ravi et al, 2016;Li et al, 2016b). This model-driven approach can make use of the temporal correlation of sensor.…”
Section: Convolutional Neural Networkmentioning
confidence: 99%
“…• Public datasets: There are already many public HAR datasets that are adopted by most researchers (e.g. (Plötz et al, 2011;Ravi et al, 2016;Hammerla et al, 2016)). By summarizing existing literature, we present several widely used public datasets in Table 3.…”
Section: Benchmark Datasetsmentioning
confidence: 99%
“…In [16], the authors proposed a human activity recognition technique based on a deep learning model designed for low power devices. The recognition gives significant contextual data for well-being.…”
Section: Related Workmentioning
confidence: 99%